The promises of presentational technology for teaching and learning - Vahid Motamedi (Journal of Education and Learning (EduLearn), 2019)
The teaching and learning styles that teachers and students apply in their teaching and learning have dramatically changed due to technological advances particularly in computer. Technological advancements are affecting the way we teach and learn. Technology has found a profound home in the world of teaching and learning. Teaching/learning technologies (TLT) have received considerable attention of many including academicians in recent years. The promises of TLT vary for the respective publics. Many insist that students today do not learn well with traditional teaching and learning methods. They argue that students require presentations that are visual and stimulating. Classroom teachers hold the key to the effective use of technology to improve learning. Whatever the varying perceptions of the promises of teaching, leaning, technology, presentation instruction in the classroom, using the Web for teaching the bulk of their course, and many other faculty are considering adopting such technologies. This paper will examine some of the advantages and disadvantages of only one type of TLT, presentational technology in the classroom, and some of the issues for faculty to consider before adopting it.